Implementation of Task-Based Language Learning Approach to Improve Pronunciation (2017)
ABSTRACT: This action research project reports how Task Based Learning approach contributed to improve eighth graders’ pronunciation in an EFL class in a public institution in Bello, Colombia. In this project, three oral tasks were developed following the three phases of Task-Based Learning proposed by Willis (1996). I collected data through a reflective log and audio recordings of the students’ presentations. The findings of this project revealed that students improved their EFL pronunciation, which was manifested in the increase of well-pronounced vowel sounds, the development of the native speakers’ imitation strategy, the preparation and the self-confidence to participate, and the awareness about the mother tongue interference.